A Historical Sketch of the Idea of Caucasian Unity and Common Defense Arrangements - Slye, Sarah (TSU-TI — THE INTERNATIONAL SCIENTIFIC JOURNAL OF HUMANITIES, 2022)
In this presentation I will provide a preliminary sketch of the idea of Caucasian political unity and common defense arrangements within the Caucasian intellectual tradition. The presentation covers the concepts of centralization, decentralization, confederalism, federalism and regionalism as expressed in the tradition of political thought in the region from the ancient and medieval to the modern period. For the ancient period, I will briefly reference certain recorded tribal alliances or joint defense arrangements, however temporary they may have been. For the medieval period, we will look at the way medieval Georgians perceived the ideal relationship between the different Caucasian nations. For the modern period, we will look at various attempts to mount a regional resistance or stage a regional uprising against the Imperial Russian or Soviet forces as well as review the debates for and against a regional federation for the Caucasus between 1860 and 1921.